StudenciCardiac arrest during acute myocardial infarction - Chrobak, Wojciech; Niedziela, Jacek; Urlik, Maciej; Gąsior, Mariusz; Nadziakiewicz, Paweł (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2008)
According to many authors coronary heart disease and especially acute myocardial infarction (AMI) is the most common cause of cardiac arrest (CA) in adults. The first hours of AMI are the time when ventricular fibrillation appears. Out-of-hospital cardiac arrest episodes take place mostly at home. Outcome in this group depends on witnesses’ reactions. In-hospital cardiac arrest due to myocardial infarction is associated with extensive heart damage, cardiogenic shock and other complications. Modern treatments of AMI have reduced the frequency of in-hospital cardiac arrest. However, for episodes of any CA prognosis is severe. Mortality oscillates between 30 and 95% and depends on rescuer performance, localization and pathomechanism of cardiac arrest.